SHOWING HOUR SEVEN SEGMENT ON COMPUTER - Henry P Henry P; Luyung Dinaini, SKom, MM Luyung Dinaini, SKom, MM (Jurnal Sistem Informasi, 2003)
This circuit is a System That Can mengetauhi Pls We Are the operating hours the computer as if we're operating a software, We Can not see the clock on the computer, whereas in our series of seven segment was biased view. So this circuit can helps us to know the time and how long We use computers. In Addition, the circuit can is Also Used to check whether the clock in our computer is appropriate or not. For data processing in this circuit, using Pascal language.